Literary activity of writers of Pidkarpatska Rus as a considerable factor in the development of the content of school humanitarian education and cultural development of the population at the beginning of the XX century - Depchynska Ivetta; Depcsinszka Ivett; Депчинська Іветта (Громадська наукова організація «Всеукраїнська асамблея докторів наук з державного управління», 2022)
Abstract. In the article the author reveals the problem of the development of literary work of writers, teachers in Pidkarpatska Rus in the period of Czechoslovakia as an important factor in the development of the content of school humanitarian education at the beginning of the XX century. The concept of humanitarian education reflects the level of social development, the system of basic humanitarian values: the value of the individual, the value of human life, moral and spiritual values, ideas about which give philosophical generalizations, psychological and pedagogical theory and practice. And as a system of knowledge, this concept reflects the totality of knowledge in the field of social sciences and related skills. In our opinion, among the disciplines of the humanities, literature is of particular importance as the art of speech, a way of forming a general human culture, its moral orientations, values, key educational competencies. In this context, the experience of building a democratic society in Transcarpathia in the interwar period (1919-1939), as well as the development of education at that time is very relevant.

A cikkben a szerző feltárja a kárpátaljai írók, tanárok irodalmi munkásságának fejlődésének problémáját Csehszlovákia időszakában, mint az iskolai humanitárius oktatásfejlesztés fontos tényezője a XX. század elején. A humanitárius oktatás fogalma tükrözi a társadalmi fejlettség szintjét, az alapvető humanitárius értékrendet: a az egyén értéke, az emberi élet értéke, az erkölcsi és szellemi értékek, amelyekről az elképzelések filozófiai általánosításokat adnak, pszichológiai és pedagógiai elmélet és gyakorlat. Ez a fogalom pedig tudásrendszerként a teljességet tükrözi a társadalomtudományi ismeretek és a kapcsolódó készségek területén.

Резюме. У статті автор розкриває проблему розвитку літературної діяльності письменників Підкарпатської Русі в період Чехословаччини як важливого чинника розвитку змісту шкільної гуманітарної освіти та культурного розвитку населення на початку ХХ ст. Поняття гуманітарної освіти відображає рівень розвитку суспільства, систему основних гуманітарних цінностей: цінність особистості, людського життя, культури, морально-духовні цінності, уявлення про які дають філософські узагальнення, психолого-педагогічна теорія і практика. І як система знань це поняття відображає сукупність знань у галузі суспільних наук та пов’язаних з ними навичок.
Літературна діяльність письменників Підкарпатської Русі як важливий фактор розвитку шкільної гуманітарної освіти краю та культурного розвитку населення початку ХХ століття
Keywords: Pidkarpatska Rus; humanitarian education; cultural development; the content of school humanitarian education; literature